2020
DOI: 10.1080/26395940.2020.1842251
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals pollution in sediment at the Omaruru River basin in Erongo region, Namibia

Abstract: This study determined the contamination levels of some heavy metals: Mn, Cr, Cu, Ni, Fe, As, and Al obtained from the delta basin of Omaruru River, using Inductively Coupled Plasma-Optical Emission Spectrophotometer (Optima 8000, Perkin Elmer). Chemical analysis showed that the sediments samples have metal concentrations ranging from 88 to 128mg/kg for Mn, 3973 to 4369mg/kg for Fe, 96 to 107mg/kg for Cr, 6 to 9mg/kg for Cu, 9 to 11mg/kg for Ni, 17 to 19mg/kg for As, and 11750 to 9002mg/kg for Al. The concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The observed variability in the study findings can be attributed to the textural properties identified, the degree and extent of the pollution sources, and the recorded water discharge at the sampling stations. The study findings, particularly the pH ranges, are slightly related to the pH values provided by Onjefu et al [86]. The average moisture content of the sediment samples ranged from 9.19 ± 0.3% to 41.46 ± 0.6%; the difference in the moisture content might be attributed to the textural properties of the sediment and other factors, such as the presence of total dissolved ions that reduce the saturation in the soil particles.…”
Section: Physical Parameterssupporting
confidence: 56%
“…The observed variability in the study findings can be attributed to the textural properties identified, the degree and extent of the pollution sources, and the recorded water discharge at the sampling stations. The study findings, particularly the pH ranges, are slightly related to the pH values provided by Onjefu et al [86]. The average moisture content of the sediment samples ranged from 9.19 ± 0.3% to 41.46 ± 0.6%; the difference in the moisture content might be attributed to the textural properties of the sediment and other factors, such as the presence of total dissolved ions that reduce the saturation in the soil particles.…”
Section: Physical Parameterssupporting
confidence: 56%
“…In Namibia, a semi-arid country, evaluation and monitoring of pollution of freshwater ecosystems are important to mitigate water shortage. This has been demonstrated by several local studies that aimed at assessing the levels of pollution due to heavy metals in marine environments (e.g [20]- [28]). However, the Orange river which extends from Lesotho through South Africa and Namibia into the Atlantic Ocean is poorly studied in Namibia, thus locally there exists limited literature on the status of metal pollution in this river.…”
Section: Introductionmentioning
confidence: 92%
“…The elucidation of the physicochemical parameters was based on the criteria of the World Health Organization (WHO). Multiple indices (CF, PLI, I geo and EF) classification used in [20] [39] as presented in Table 2, was adopted in this work to categorize pollution level, nature of enrichment and sediment quality.…”
Section: Metal Assessment In Sedimentsmentioning
confidence: 99%
“…The location of Oshikoto region (where anthill soil sample was collected) on the Namibian map (Source: Thomson, 2018). Open Journal of Soil Science potential (ORP) using a portable meter (HI9811-5, Hanna instrument) [21].…”
Section: ) Measurement Of Anthill Soil Physicochemical Parametersmentioning
confidence: 99%